Class III malocclusion with severe anteroposterior discrepancy - Rizzatto,Susana Maria Deon (2012)
This study aims at reporting the clinical case of a patient with Class III skeletal malocclusion with severe maxillary deficiency, producing a reduced midface associated with severe mandibular prognathism. The pre-surgical orthodontic preparation was composed mainly by dentoalveolar expansion and repositioning of the incisors in the lower arch. Then, a combined maxillary and mandibular orthognathic surgery was performed. The treatment objectives were achieved, with significant improvement in facial esthetics and occlusion, followed by post-treatment stability. This case was presented to the Brazilian Board of Orthodontics and Facial Orthopedics (BBO), as part of the requirements for obtaining the title of Diplomate by BBO.